Visual Object Categorization based on Gabor Filter Generalization Via K-Means Clustering - Ayad, Hayder; Norul Huda Sheikh Abdullah, Siti; Abdullah, Azizi (International Journal of Engineering and Technology, 2019)
Content based object recognition systems need informative image properties to obtain good performance results. Filter bank such as Gabor filters is believed to be one of the most popular methods for complete characterization of images by having some important properties such as selectivity to orientation, scale, frequency and smooth parameters. Furthermore, such properties are very effective for compact image description and analysis. However, these functions show a strong dependence on a certain number of different parameter values. Hence, the different filter parameters values used to construct the functions may give different filter responds or properties. Besides, the large number of these filters leads to expensive computation to create maps for feature extraction, thus it is necessary to reduce the number of candidates and identify subset of effective and discriminative filters to avoid overfitting and hinder generalization performance. In this paper, we first compute Gabor filters using a set of different values for filter parameters. After that, the k-means clustering algorithm is used to group these filter responds into k different clusters. Next the k different clusters are used to convolve images and the edge histogram then apply to the filter outputs for image description. After that, we combine all outputs of image descriptors using SVMs. Experiment results on 20 and 101 classes of the Caltect-101 object database show that the method significantly outperforms using the standard Gabor filter approach.Â